2023
DOI: 10.1037/tra0001229
|View full text |Cite
|
Sign up to set email alerts
|

The role of strength-based parenting, posttraumatic stress, and event exposure on posttraumatic growth in flood survivors.

Abstract: Objective: The present study examined the role of posttraumatic stress symptoms (PTSS), strengthbased parenting (SBP), and event exposure on posttraumatic growth (PTG) in Peruvian flood survivors. Method: After contacting local authorities, 1,077 adult participants were surveyed 1 year after the flood. Correlation, moderation, and mediation analyses were conducted to determine relationships between variables. Results: Flood survivors experienced both PTSS and PTG. Additionally, event exposure directly facilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…A retrospective study of nearly 4,000 U.S. adults found that parental warmth during childhood was associated with positive relations with others and personal growth a decade later (Chen et al, 2019). Another study of flood survivors found a positive relation between strength-based parenting and postloss growth (Zavala et al, 2023). Informed by these findings and Kilmer et al’s (2014) assumptions, we hypothesized that parental warmth at 11-month follow-up would be related to postloss growth (b2 and c5 paths).…”
Section: The Cascade Model Of Fbp’s Effect On Postloss Growthmentioning
confidence: 99%
“…A retrospective study of nearly 4,000 U.S. adults found that parental warmth during childhood was associated with positive relations with others and personal growth a decade later (Chen et al, 2019). Another study of flood survivors found a positive relation between strength-based parenting and postloss growth (Zavala et al, 2023). Informed by these findings and Kilmer et al’s (2014) assumptions, we hypothesized that parental warmth at 11-month follow-up would be related to postloss growth (b2 and c5 paths).…”
Section: The Cascade Model Of Fbp’s Effect On Postloss Growthmentioning
confidence: 99%
“…This has resulted in an increased interest in the research area of IPV [ 25 , 56 ], leading to an international, steady increase in the number of publications on the subject over the last 20 years [ 25 ]. Research on PTG has been conducted in various fields of the literature of trauma, such as transportation accidents or other accidental injuries [ 57 , 58 , 59 ], natural disasters [ 60 , 61 , 62 , 63 , 64 , 65 ], interpersonal experiences [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ], medical problems [ 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ], and other life experiences [ 87 , 88 , 89 , 90 ]. Even so, when it comes to research on PTG following IPV among female survivors, there seems to be a severe lack of literature [ 91 ].…”
Section: Introductionmentioning
confidence: 99%